Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

Quantum dot based immunosensor using 3D circular microchannels fabricated in PDMS - Morarka, Amit; Agrawal, Shailaja; Kale, Sonia; Kale, Anup; Ogale, Satishchandra B.; Paknikar, Kishore; Bodas, Dhananjay S. (Biosensors & Bioelectronics, 2011)
Microchannel is basic functional component of microfluidic chip and every step-forward of its construction technique has been receiving concern all over the world. The present work describes a novel, rapid and simple fabrication technique for building 3D microchannels in poly(dimethyl siloxane) (PDMS) elastomer. These microchannels were used for rapid detection of antigens (E. coli) by quantum dot (QD) based approach. Luminescent QD (CdTe) were synthesized by aqueous method and characterized using high resolution transmission electron microscopy (HRTEM), fluorescence spectroscopy and X-ray diffraction (XRD). The QDs were functionalized with anti-E. coli antibodies for immuno-detection. The reported process allowed easier and faster method of fabrication of circular 3D micochannels and demonstrated their potential use in an immuno-biosensor device. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Capillary driven flows; Circular microfluidics; Immunosensor; QDs

Quantum dot bio-conjugate: as a western blot probe for highly sensitive detection of cellular proteins - Kale, Sonia; Kale, Anup; Gholap, Haribhau; Rana, Abhimanyu; Desai, Rama; Banpurkar, Arun G.; Ogale, Satishchandra; Shastry, Padma (Journal of Nanoparticle Research, 2012)
In the present study, we report a quantum dot (QD)-tailored western blot analysis for a sensitive, rapid and flexible detection of the nuclear and cytoplasmic proteins. Highly luminescent CdTe and (CdTe) ZnS QDs are synthesized by aqueous method. High resolution transmission electron microscopy, Raman spectroscopy, fourier transform infrared spectroscopy, fluorescence spectroscopy and X-ray diffraction are used to characterize the properties of the quantum dots. The QDs are functionalized with antibodies of prostate apoptosis response-4 (Par-4), poly(ADP-ribose) polymerases and beta actin to specifically bind with the proteins localized in the nucleus and cytoplasm of the cells, respectively. The QD-conjugated antibodies are used to overcome the limitations of conventional western blot technique. The sensitivity and rapidity of protein detection in QD-based approach is very high, with detection limits up to 10 pg of protein. In addition, these labels provide the capability of enhanced identification and localization of marker proteins in intact cells by confocal laser scanning microscopy.
Keywords: Detection; Imaging; nanomedicine; quantum dot; Rapid; sensors; Western blot

Fluorescent cadmium telluride quantum dots embedded chitosan nanoparticles: a stable, biocompatible preparation for bio-imaging - Ghormade, Vandana; Gholap, Haribhau; Kale, Sonia; Kulkarni, Vaishnavi; Bhat, Suresh; Paknikar, Kishore (Journal of Biomaterials Science-Polymer Edition, 2015)
Fluorescent cadmium telluride quantum dots (CdTe QDs) are an optically attractive option for bioimaging, but are known to display high cytotoxicity. Nanoparticles synthesized from chitosan, a natural biopolymer of beta 1-4 linked glucosamine, display good biocompatibility and cellular uptake. A facile, green synthetic strategy has been developed to embed green fluorescent cadmium telluride quantum dots (CdTe QDs) in biocompatible CNPs to obtain a safer preparation than `as is' QDs. High-resolution transmission electron microscopy showed the crystal lattice corresponding to CdTe QDs embedded in CNPs while thermogravimetry confirmed their polymeric composition. Electrostatic interactions between thiol-capped QDs (4nm, -57mV) and CNPs (\~300nm, +38mV) generated CdTe QDs-embedded CNPs that were stable up to three months. Further, viability of NIH3T3 mouse fibroblast cells in vitro increased in presence of QDs-embedded CNPs as compared to bare QDs. At the highest concentration (10 mu g/ml), the former shows 34 and 39% increase in viability at 24 and 48h, respectively, as compared to the latter. This shows that chitosan nanoparticles do not release the QDs up to 48h and do not cause extended toxicity. Furthermore, hydrolytic enzymes such as lysozyme and chitinase did not degrade chitosan nanoparticles. Moreover, QDs-embedded CNPs show enhanced internalization in NIH3T3 cells as compared to bare QDs. This method offers ease of synthesis and handling of stable, luminescent, biocompatible CdTe QDs-embedded CNPs with a favorable toxicity profile and better cellular uptake with potential for bioimaging and targeted detection of cellular components.
Keywords: Biocompatible; bioimaging; CdTe quantum dots; chitosan nanoparticles; Toxicity